Vinylene‐Linked 2D Conjugated Covalent Organic Frameworks by Wittig Reactions. (9th November 2022) - Liu, Yannan; Fu, Shuai; Pastoetter, Dominik L.; Khan, Arafat Hossain; Zhang, Yingying; Dianat, Arezoo; Xu, Shunqi; Liao, Zhongquan; Richter, Marcus; Yu, Minghao; Položij, Miroslav; Brunner, Eike; et al.
Abstract: Vinylene‐linked two‐dimensional covalent organic frameworks (V‐2D‐COFs) have shown great promise in electronics and optoelectronics. However, only a few reactions for V‐2D‐COFs have been developed hitherto. Besides the kinetically low reversibility of C=C bond formation, another underlying issue facing the synthesis of V‐2D‐COFs is the attainment of high ( E )‐alkene selectivity to ensure the appropriate symmetry of 2D frameworks. Here, we tailor the E / Z selectivity of the Wittig reaction by employing a proper catalyst (i.e., Cs2 CO3 ) to obtain more stable intermediates and elevating the temperature across the reaction barrier. Subsequently, the Wittig reaction is innovatively utilized for the synthesis of four crystalline V‐2D‐COFs by combining aldehydes and ylides. Importantly, the efficient conjugation and decent crystallinity of the resultant V‐2D‐COFs are demonstrated by their high charge carrier mobilities over 10 cm 2  V −1  s −1, as revealed by non‐contact terahertz (THz) spectroscopy. Abstract : The Wittig reaction is demonstrated as novel synthetic strategy for the synthesis of crystalline unsubstituted vinylene‐linked 2D conjugated covalent organic frameworks through the attainment of high ( E )‐alkene selectivity. Ultrafast THz spectroscopy discloses state‐of‐the‐art charge‐transport properties of as‐prepared V‐2D‐COFs as a result of electron delocalization in the fully conjugated frameworks.